2015
DOI: 10.1038/sc.2015.149
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fatigue and participation in spinal cord injury

Abstract: Study design: Cross-sectional national survey. Objectives: To explore the association between fatigue and community participation frequency and provide an adjusted model of the relationship including important covariates. Setting: Canada; Community. Methods: Data were obtained from the Rick Hansen Spinal Cord Injury Registry Community Survey. We used multi-variable regression analyses with hierarchical backward elimination, including variable specification, interaction assessment and confounding assessment. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Among police officers, increase in fatigue score was associated with a 33% increase in prevalence of injury [ 15 ]. In a study of Canadian, fatigue has a statistically significant negative association with participation for individuals with spinal cord injury [ 18 ]. Significant associations between fatigue and occupational injuries have been demonstrated, but little is known about the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Among police officers, increase in fatigue score was associated with a 33% increase in prevalence of injury [ 15 ]. In a study of Canadian, fatigue has a statistically significant negative association with participation for individuals with spinal cord injury [ 18 ]. Significant associations between fatigue and occupational injuries have been demonstrated, but little is known about the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, findings from a 5-year follow-up study showed that beyond respiratory function impairments and reduced ability to cough (30.9% of the patients had a forced vital capacity (FVC) below the 80% predicted value, 35.9% poor or moderate self-reported cough strength), 18.4% of the patients reported rest dyspnoea and 29.0% during activity, being associated with worse health-related quality of life (Postma et al, 2016). Patients with SCI also report pain and fatigue as relevant symptoms, with a statistically significant negative association with reduced mobility, participation, and satisfaction with life (Marcondes et al, 2016;Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1 Fatigue has a negative association with participation in life activities after SCI. 3 Fatigue may also have negative effects on involvement in rehabilitation after SCI. 4 Use of mobility aids and wheelchairs may be adversely affected by fatigue.…”
Section: Introductionmentioning
confidence: 99%